Factors associated with the relationship between screen time and increased anxiety in children and adolescents during the COVID-19 pandemic: an integrative review (Research, Society and Development, 2022)
Objective: To analyze the factors involved in the relationship between increased screen time and the presence of anxiety in children and adolescents during the COVID-19 pandemic period. Methods: This is an integrative literature review of scientific articles on increased screen time and anxiety in children and adolescents during the COVID-19 pandemic period. Articles from the Scielo, PubMed, Medline, Capes and Lilacs databases were analyzed during the month of April 2022. The search was limited to articles in Portuguese and English, published during the period of the COVID-19 pandemic, complete or available in full, and with reference to the topic. Results: The initial search in the databases resulted in a total of 89 publications. After reading the titles and abstracts, 14 were selected for full reading and, of these, 8 were chosen for the study. Conclusion: It is evident, therefore, the increase in anxiety as a negative impact of the excessive use of screens during the COVID-19 pandemic and the associated factors. Despite the existence of scarce literature on the subject in the period of time in question, the content presented is just one step to demonstrate the importance of the need for an active discussion on the subject.